2015
DOI: 10.1038/bmt.2015.288
|View full text |Cite
|
Sign up to set email alerts
|

New strategies of DLI in the management of relapse of hematological malignancies after allogeneic hematopoietic SCT

Abstract: DLI is an effective strategy for patients with recurrent hematological malignancies after allogeneic hematopoietic SCT (allo-HSCT). DLI has been widely applied to boost the graft vs tumor (GVT) or GVL effects. However, given the potentially severe complications associated with conventional DLI and transient GVL effect, new strategies for DLI are emerging. In this review, we have discussed the recent important studies on DLI as a prophylactic or therapeutic modality for relapsed hematological disorders after al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 106 publications
1
19
0
Order By: Relevance
“…Nevertheless, the results of the present study indicate that UDLI has efficacy in inducing a GVT effect, even at 100 days after treatment. As reported previously, the present study revealed that UDLI was most effective for the treatment of CML [2,4,8,19], although recent reports have shown that post-transplantation TKIs might be effective for relapse as well as reducing the incidence of relapse for patients with Philadelphia-positive leukemia [20][21][22][23][24]. A particularly strong effect was also observed in patients with low tumor burden, such as those with cytogenetic/molecular relapse or the onset of acute GVHD after UDLI.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Nevertheless, the results of the present study indicate that UDLI has efficacy in inducing a GVT effect, even at 100 days after treatment. As reported previously, the present study revealed that UDLI was most effective for the treatment of CML [2,4,8,19], although recent reports have shown that post-transplantation TKIs might be effective for relapse as well as reducing the incidence of relapse for patients with Philadelphia-positive leukemia [20][21][22][23][24]. A particularly strong effect was also observed in patients with low tumor burden, such as those with cytogenetic/molecular relapse or the onset of acute GVHD after UDLI.…”
Section: Discussionsupporting
confidence: 70%
“…Nevertheless, because mortality associated with a second allo-HSCT for relapsed recipients is considered to be much higher, DLI therapy may represent a viable alternative to second allo-HSCT. Thus, DLI has been applied in the treatment of various hematological malignancies [6][7][8], such as leukemias [9,10], lymphoma [11][12][13], and myeloma [14,15]. In particular, patients who have relapsed after unrelated allo-HSCT because of lack of HLA-matched related sibling donors may also benefit from unrelated DLI (UDLI) [16].…”
Section: Introductionmentioning
confidence: 99%
“…Those that can induce graft-versus-leukemia effects are under development [43]. Until their introduction into real clinical practice, currently available cellular therapy for the induction of GVHD aiming to evoke graft-versus-leukemia effects could be considered even at the expense of morbidities related to GVHD [44]. For disease that outpaces the development of GVHD, pretransplant debulking treatment or post-transplant maintenance chemotherapy could be an option [19,45,46].…”
Section: Discussionmentioning
confidence: 99%
“…In the field of HPC transplantation, the target is the collection of CD34+ cells. 6 In contrast, in other cell therapy protocols, the target is the collection of lymphocytes for donor lymphocyte infusions 21 or the collection of monocytes in order to generate monocyte-derived dendritic cells. 4 In ECP, there is no minimum of cells to collect because there are contradictory results regarding the amount of cells treated and the response to ECP.…”
Section: Discussionmentioning
confidence: 99%